Central Venous-to-Arterial Carbon Dioxide Gradient as a Marker of Occult Tissue Hypoperfusion after Major Surgery. Issue 5 (September 2015) - Silbert, B. I.; Litton, E.; Ho, K. M.
The central venous-arterial carbon dioxide tension gradient ('CO2 gap') has been shown to correlate with cardiac output and tissue perfusion in septic shock. Compared to central venous oxygen saturation (SCV O2 ), the CO2 gap is less susceptible to the effect of hyperoxia and may be particularly useful as an adjunctive haemodynamic target in the perioperative period. This study investigated whether a high CO2 gap was associated with an increased systemic oxygen extraction (O2 ER >0.3) or occult tissue hypoperfusion in 201 patients in the immediate postoperative period. The median CO2 gap of all patients was 8 mmHg (IQR 6 to 9), and a large CO2 gap was very common (>6 mmHg in 139 patients [69%], 95% CI 63 to 75; >5 mmHg in 170 patients [85%], 95% CI 79 to 89). A CO2 gap <5 mmHg had a higher sensitivity (93%) and negative predictive value (74%) than a CO2 gap <6 mmHg in excluding occult tissue hypoperfusion. Of the four variables that were predictive of an increased O2 ER in the multivariate analysis—CO2 gap, arterial pH, haemoglobin and arterial lactate concentrations—the CO2 gap (odds ratio 4.41 per mmHg increment, 95% CI 1.7 to 11.2, P =0.002) was most important and explained about 34% of the variability in the risk of occult tissue hypoperfusion. In conclusion, a normal CO2 gap (<5 mmHg) had a high sensitivity and negative predictive value in excluding inadequate systemic oxygen delivery and may be useful as an adjunct to other haemodynamic targets in avoiding occult tissue hypoperfusion in the perioperative setting when high inspired oxygen concentrations are used.